Model of excellence : from individuals to dynamic capabilities - Sivusuo, Jaakko; Sivusuo, Henry; Takala, Josu (University of Primorska, 2018)
Nowadays dynamic capabilities, sustainable competitive advantage and competition are normal elements in today’s business world. Organizations are constantly trying to survive in competition. This study is building a model which aims to clarify competitive advantage from the point of organization and its’ individuals. This study is based on constructive method and as a result Model of excellence is build. This model consists two separate sections; value-driven and norm-driven. This model is going to clarify how organizations are able to gain competitive advantage in turbulent environments. Model is also one tool for dynamic capabilities and it can be used for assessing organizations’ maturity. Model of excellence emphasizes the role of individuals for building and maintaining sustainable competitive advantage. Case study is also included. This study reveals how to use model of excellence in the field of project management. Case study shows how project management roles can be implement in Model of excellence.
Keywords: leadership (activity); organisations (systems); enterprises; business; change management (leadership); strategic leadership; self-evaluation; quality awards; development (active); dynamic capabilities; fi=Tuotantotalous|en=Industrial Management|